National Food Systems: Inclusive transformation for healthier diets - McDermott, John (2020)
John McDermott SEMINAR Virtual Event --Discussion of the 2020 Global Food Policy Report Co-Organized by the Ministry of Foreign Affairs, Government of the Netherlands, IFPRI, and Food & Business Knowledge Platform APR 28, 2020 - 10:00 AM TO 11:15 AM EDT